Magnetically-Induced Pressure Generation in Magnetorheological Fluids under the Influence of Magnetic Fields - Purwadi Joko Widodo (MDPI AG, 2021)
This study aims to observe the magnitude of the Magnetorheological Fluids (MRFs) pressure due to the application of a magnetic field. This was accomplished by placing the MRFs in a U-shaped tube, then applying a magnetic field generated by a magnetic coil. A finite element simulation for the magnetic field was carried out to estimate the magnetic field strength generated by the coil variable to the current input given in the simulated apparatus. Changes in MRFs pressure were recorded using a data logger to better observe the fluid pressure phenomena occurring in the MRFs with respect to current input variations. The results showed that the magnetic field influences the MRFs fluid pressure proportionally. The slope is not constant as the magnetic field effect to the fluid pressure gets stronger when the current input is higher. However, there are also an adverse effect of heat generated in the coil in higher current, which results in coil performance degradation and reduces the magnetic field strength.